Penerapan GMP dan SSOP dalam Proses Produksi Rendang Daging di Produsen Rendang Istana Rendang Jambak - V. Indriani; A. Apriantini; T. Suryati (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
Rendang is a Minangkabau typical food made from meat cooked with coconut milk and additional spices for 4-6 hours using a wood stove and a semi-closed place, where the rendang is made potentially contaminated with contamination during production. This study aims to evaluate the application of the basic requirements of food safety standards, namely GMP and SSOP during the production process at the rendang producer, Istana Rendang Jambak. Data were taken based on observations and interviews of workers and owners. The assessment of conformity with the application of GMP in rendang producers, Istana Rendang Jambak, obtained a score of 34.17%-85.00%, with a deviation value of 213 from the overall value of 468. The assessment of conformity with the application of SSOP obtained a value of 0.00%-68.75%, with a deviation value of 79 from the overall value of 120. Rendang Palace Jambak is sufficient to meet the principles of GMP, but does not meet FDA requirements regarding SSOP.